Molecular and Physiological Basis of Nematode Survival - Perry, Roland N (CABI, 2014)
Nematodes are a remarkable group of invertebrates; there are over 25,000 described species, including free-living, animal-parasitic and plant-parasitic species and, of all groups of animals on the planet, they are the most success- ful. Not only do species of nematodes live in a wide variety of habitats, from hot water springs and Antarctic tundra to habitats in plants and animals as parasites, but many species also show an astonishing ability to survive severe adverse environmental conditions. The early descriptions of nematodes date back over 3000 years and relate to nematode parasites of man. The damaging economic and social impacts of animal-parasitic species on man and other animals have long been recognized. The impact of plant-parasitic nematodes has been realized only relatively recently, but now the nematode pests of agricultural crops are known to cause considerable economic loss and, espe- cially in developing countries, adverse social impact. One of the reasons for the success of nematodes as a group is their ability to survive adverse condi- tions by entering a resistant, dormant metabolic state. This survival ability has fascinated scientists for many years.